Five ways to get a grip on the shortcomings of logic models in program evaluation (Canadian Medical Education Journal, 2021)
Logic models are perhaps the most widely used tools in program evaluation work. They provide reasonably straightforward, visual illustrations of plausible links between program activities and outcomes. Consequently, they are employed frequently in stakeholder engagement, communication, and evaluation project planning. However, their relative simplicity comes with multiple drawbacks that can compromise the integrity of evaluation studies. In this Black Ice article, we outline key considerations and provide practical strategies that can help those engaged in evaluation work to identify and mitigate some limitations of logic models